Computational evaluation of AKT2 mutations reveals R274H and R467W as potential drivers of protein instability and inhibitor resistance in cancer therapy - Sadia Afrin Runa; Mahafujul Islam Quadery Tonmoy; Md. Ashiqul Islam; Md. Aminul Islam (PLoS ONE, 2025)
Cancer remains a leading cause of mortality worldwide, with genetic alterations such as single nucleotide polymorphisms (SNPs) playing a critical role in tumor progression and therapy resistance. Non-synonymous SNPs (nsSNPs) in AKT2, a key kinase in the PI3K/AKT signaling pathway, can impact protein structure and function, leading to reduced efficacy of targeted cancer therapies. This study employs computational approaches to investigate the structural and functional consequences of nsSNPs in the AKT2 and their impact on inhibitor interactions. Three structurally and functionally significant nsSNPs (Y265N, R274H, and R467W) were identified where only R274H and R467W were associated with reduced inhibitor binding. R274H, and R467Wwere found to disrupt key molecular mechanisms, including metal binding, loss of allosteric sites, and alterations in post-translational modifications. Molecular docking revealed that R274H, in kinase domain, disrupts key hydrogen bonds with THR292 and GLU279, leading to more flexible binding pocket and significantly reduced binding affinity for Capivasertib and Ipatasertib. Similarly, R467W, in AGC-kinase C-terminal domain, causes the loss of hydrogen bonds with THR292, ASN280, and GLU279, leading to decreased binding affinity for Akt1/Akt2-IN-1, Capivasertib, and Ipatasertib inhibitors. MD simulations further demonstrated that R274H and R467W caused substantial structural deviations and increased residue flexibility, with R467W exhibiting the most pronounced destabilizing effect. These findings suggest that these mutations may contribute to inhibitor resistance by weakening inhibitor interactions and destabilizing the protein-inhibitor complex. This study underscores the importance of genetic screening in optimizing cancer treatment and highlights the need for mutation-specific therapeutic strategies targeting AKT2.